The Little mermaid [videorecording] - Ashman, Howard; Clements, Ron; Muskin, John (Walt Disney, 1989)
A little sea princess, longing to be human, trades her mermaid's tail for legs, hoping to win the love of a prince and earn an immortal soul for herself.